2020
DOI: 10.1108/ci-05-2019-0038
|View full text |Cite
|
Sign up to set email alerts
|

General contractors’ experience using off-site structural framing systems

Abstract: Purpose This paper aims to examine general contractors’ experiences of using off-site manufactured structural framing systems. This engaged a single-case study using a qualitative methodology to identify expected benefits, actual benefits and challenges of such systems. Design/methodology/approach A single-case study approach evaluated general contractors’ experience of using a manufactured structural framing system. Qualitative data were collated and analyzed from industry domain experts to determine common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Close coordination between stakeholders is crucial to reduce issues pertaining to the OSM process (Heng et al , 2011). Previous research has highlighted collaboration uncertainties such as designers’ lack of awareness on safety requirements (Kim et al , 2011) and site logistics constraints due to poor communication (Killingsworth et al , 2020). Hwang et al (2018) found that OSM requires extensive collaboration prior to and during the project and suggested to use building information modelling to improve collaboration and communication among stakeholders.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Close coordination between stakeholders is crucial to reduce issues pertaining to the OSM process (Heng et al , 2011). Previous research has highlighted collaboration uncertainties such as designers’ lack of awareness on safety requirements (Kim et al , 2011) and site logistics constraints due to poor communication (Killingsworth et al , 2020). Hwang et al (2018) found that OSM requires extensive collaboration prior to and during the project and suggested to use building information modelling to improve collaboration and communication among stakeholders.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Heng et al (2011) utilises virtual prototyping technology with the aid of IKEA model towards the safety of prefabricated construction work. Application of robotics or machinery for unloading prefabricated component during on-site proceedings were suggested to improve safety specially when on-site installations are affected by adverse weather conditions (Killingsworth et al , 2020). With the development of information technology, emerging technologies can be synchronised with various safety management aspects such as for improving the work site, crane operations and managing the workforce (Yingbo et al , 2019; Lu and Zhu, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When it comes to safety research in off-site construction, topics explored include an analysis of risks in off-site versus hypothetical on-site construction scenarios for the same building components (Ahn et al, 2020); off-site construction facilities to determine root causes of safety incidents (Fard et al, 2017); and behaviours in off-site environments to predict safety outcomes (Liu et al, 2019). Additionally, much of the research surrounding safety risk assessments in offsite construction is qualitative and summarizes findings from expert opinions (Killingsworth et al, 2020) about the perceived benefits of the off-site approach.…”
Section: Introductionmentioning
confidence: 99%
“…Realisation of this lean ideal will bring construction closer to series production (i.e., manufacturing). Pan and Sidwell (2011) Tam, et al (2015) Killingsworth, Mehany and Ladhari (2021 As use of OSF continues to grow, it becomes increasingly important to create a smooth flow from raw materials arriving in the factory to the installation of the resulting sub-assemblies on-site. Predictable, Just-in-time ( JIT) production in a factory is possibly easier than it is on-site, yet it is far from simple.…”
Section: Introductionmentioning
confidence: 99%